2001
DOI: 10.1111/j.1365-2621.2001.tb15191.x
|View full text |Cite
|
Sign up to set email alerts
|

Pork Quality is Affected by Early Postmortem Phosphate and Bicarbonate Injection

Abstract: The ability of sodium polyphosphate (P) to alter postmortem pH declines and pork quality was investigated. Hams from electrically stimulated carcasses were injected 18 min postmortem with P or sodium bicarbonate (SB). P and SB reduced (P Ͻ Ͻ Ͻ Ͻ Ͻ 0.001) pH decline and improved (P Ͻ 0.05) color. P and SB administration improved water-holding capacity as indicated by reductions (P Ͻ 0.05) in drip loss, thaw loss, and cooking loss values. P and SB also reduced (P Ͻ Ͻ Ͻ Ͻ Ͻ 0.001) shear values. These data showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 22 publications
3
29
3
Order By: Relevance
“…The CIE * values of C were significantly higher than B EW or B PE ( = 0.03) but showed no statistical difference compared to B ( = 0.06, Table 1). The decrease in lightness as a result of brine injection in muscle products is well documented [16,21,26,35]. Previous study reported that CIE * values of catfish fillets that were injected with agglomerated phosphates were lower than noninjected fillets [26].…”
Section: Colormentioning
confidence: 97%
See 2 more Smart Citations
“…The CIE * values of C were significantly higher than B EW or B PE ( = 0.03) but showed no statistical difference compared to B ( = 0.06, Table 1). The decrease in lightness as a result of brine injection in muscle products is well documented [16,21,26,35]. Previous study reported that CIE * values of catfish fillets that were injected with agglomerated phosphates were lower than noninjected fillets [26].…”
Section: Colormentioning
confidence: 97%
“…There is a growing amount of literature on the ability of low salt brines incorporated through multineedle injection technology to improve the quality of whole muscle beef, pork, and poultry products [14][15][16][17][18][19][20][21]. Low salt brines are typically 2 Journal of Food Quality formulated to have less than 5% NaCl and used at levels just sufficient to impact whole muscle protein functionality without altering flavor/appearance [14,15,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major portion of pork produced in the United States and some in Canada undergoes moisture enhancement procedures (Mandell & McEwen, 2011). Moisture enhancement of fresh pork is thought to improve eating quality by increasing juiciness and tenderness (Brewer, Gusse, & McKeith, 1999;Sheard, Nute, Richardson, Perry & Taylor, 1999;Smith, Simmons, McKeith, Bechtel, & Brady, 1984;Wynveen et al, 2001). Additionally, injection of brine may improve tolerance to some cooking abuse (Baublits, Meullenet, Sawyer, Mehaffey & Saha, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, the use of alkaline salts such as bicarbonates has gained a certain interest (Petracci et al, 2013a). The first studies were focused on using bicarbonate to minimize the problem of pale, soft and exudative (PSE) in pork (Kauffman et al, 1998;Van Laack et al, 1998;Wynveen et al, 2001) and poultry (Woelfel and Sams, 2001;Alvarado and Sams, 2003). More recent studies found that sodium bicarbonate was able to reduce shear force and improve yield of enhanced poultry meat (Sen et al, 2005;.…”
Section: Introductionmentioning
confidence: 99%